Expediente ("Revista Gestión y Conexiones", 2014)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2014.3.1.7854.1-4. Apresenta a 3a. edição da Revista Gestão & Conexões (Management and Connections Journal), v3, n1, jan./jun. 2014.